THE EFFECT OF WARMING COMPRESSES IN LOWERING REUMATIC PAIN IN ELDERLY AT TRESNA WERDHA HOUSEHOLD SOCIAL PROTECTION BOGOR: PENGARUH PEMBERIAN KOMPRES HANGAT TERHADAP PENURUNAN NYERI PADA LANSIA YANG MENGALAMI REMATIK DI SUB UNIT RUMAH PERLINDUNGAN SOSIAL TRESNA WERDHA BOGOR - Nining Fitrianingsih (Wijaya Husada, 2019)
The Background of research is according to Social Assistance of Seniors erderly in Indonesia (ASLUT)report that the number of diseases directly reported by erderly in 2013. according to gender about 30.34% of men and 35.04% of women are suffer from rheumatism, 18.00% of men and 24,45% of women are suffer of hypertension, 5.41% of men and 6.29% of women are suffer of cataracts, 6.02% of men and women 4.51% are suffer of asthma, and 2.94% of men and 2.89% of women are suffer of heart disease. The Purpose of Study is identify the effect of giving warm compress pain reduction towards elderly whom experience rheumatism in the Sub Unit of the Protection house Tresna Werdha Bogor. The Method of the design research is quasi experiment research which used One Group Pre and Posttes Design. Sampling of this research is method or technique total sampling with the number of thirty two elderly. Based on the result of frequency distribution of rheumatic pain level, before being conducted warm compress was found the result measurement of severe pain scale with number of six people (37,6%), moderate pain eight people (50%) and light pain two people (12,5%), The level of arthritic pain after being conducted warm compress was found the result of measuring the scale. numbers moderate pain eight people (50, 1%), light pain eight people(50, 1%) The result of statistical T dependent was found P value 0.001 while α = 0.05 .So, P Value <α then H0 is rejected which means there was a difference of pain scale between before giving warm compress compared .And after giving warm compress to elderly with arthritis at Social Institution TresnaWerdha Bogor. This conclusion of research there was influence of giving warm compress to the decrease of pain for elderly who experienced Rheumatism in Household Protection Tresna Werdha Bogor. The Suggestion was to give the information about the level of work performance of nursing undergraduate education. so that, the hospital can further develope of human resources in the field of nursing.